Quentin Tarantino : du cinéma d’exploitation au cinéma - Philippe Ortoli (Transatlantica)
It is fairly obvious that Tarantino has contributed to making exploitation cinema, if not universally popular, at least acceptable to a wider audience than its initial niche fans. So much so that, following on the success of Pulp Fiction (1994), critics and scholars who previously frowned upon exploitation cinema were now displaying vast knowledge of these films. How has this (sometimes awkward) position suddenly become a necessity? This first observation should not be limited to the sociological perspective that has often been adopted since Reservoir Dogs (1992). Indeed, the films of Tarantino do not so much promote a pantheon of films that differs from that erected by the archeologists of cinema, but are driven by a desire to revisit the categories of film history, and thus of art history, ultimately leading to a redefinition of the very object of this quest: cinema, of course, and more generally, the image itself. This desire is developed in a variety of projects, the most audacious being, no doubt, the view of exploitation cinema as a singular expression of cinema because of its capacity to make of repetition and difference both a defining principle and an object. In so doing, this view, which, though widely shared, has never been revealed to this extent, destroys the boundaries cautiously upheld by the keepers of the temples of cinephilia and sociology.